Anatomical origin of dendritic cells determines their life span in peripheral lymph nodes. - Ruedl, C; Koebel, P; Bachmann, M; Hess, M; Karjalainen, K (2000)
Dendritic cells (DCs) exhibit considerable heterogeneity in their anatomical location, surface phenotype, and functional properties. In this study, we demonstrate that peripheral lymph nodes contain at least four major, functionally separable, and independently derived, DC subsets, which can be clearly demarcated by their CD11c, CD40, and CD8 expression pattern. Surprisingly, all DCs derived directly from the bone marrow, the myeloid- and the lymphoid-related subsets, turned over fast with t(1/2) of a couple of days. In contrast, DCs exported from the skin, both dermal and epidermal, accumulated 3- to 4-fold slower, turnover that is dramatically increased by cutaneous inflammation.